Analisis Kesenjangan Dimensi Kualitas Layanan Berdasarkan Persepsi Manajemen dan Persepsi Pasien pada Unit Rawat Inap di Rumah Sakit Umum Daerah Dokter Abdul Aziz Singkawang Kalimantan Barat - Sunanto, Sandra; Nandiwardhana, Abraham (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2005)
Creating consumer satisfaction is really important for company to create its competitiveness. Hospital as a service company must deliver the best service to her patients by designing and delivering good service quality which is including tangibles, reliability, responsiveness, assurance, and emphaty.